Screening of UCG chemical reactions and numerical simulation up-scaling of coal seam from laboratory models - Otoshi, Areji (Taylor and Francis Ltd., 2022)
Underground coal gasification (UCG) is a promising option for utilising deep-seated coal for the in-situ production of syngas. In this study, we modelled and screened the chemical reactions using the previous laboratory UCG experiments to investigate the complicated chemical reaction processes to apply them to field scale UCG operations. First, we constructed 1D and 3D numerical models by matching simulation with the laboratory coal combustion and gasification experiments involving a combustion tube test and then physically scaled the 3D experiments reported by Thorsness et al. and Stańczyk et al., respectively. We considered 5 chemical reactions from 12 chemical reactions by matching simulation to the experimental results. We adjusted the chemical reaction parameters used in our numerical simulations to match those of the experimental data. The numerical simulation results show that the proposed model can be applied in the laboratory as well as in the field-scale UCG operations to predict gasification behaviours, especially the temperature distribution, gas production rate, and gas composition. © 2021 Informa UK Limited, trading as Taylor & Francis Group.